The Politics of Bureaucracy : an Introduction to Comparative Public administration - Peters, B. Guy. (Abingdon ; New York : Routledge, 2010)
"Written by a leading authority in the field, this comprehensive exploration of the political and policy-making roles of public bureaucracies is now available in a fully revised sixth edition, offering extensive, well documented comparative analysis of the effects of politics on bureaucracy. New to the 6th edition: more international case studies on North America, Western and Eastern European and Asian countries; discussion of how governments have been developing strategies to enhance co-ordination and coherence across their programmes; analysis of the use of performance management in public administration; more tables, case studies and internet links; and extensive revision and updating to take into account the wealth of new literature that has emerged in recent years, including a discussion of E-Governance and analysis of 'new public management'. Drawing on evidence from a wide variety of political systems, The Politics of Bureaucracy continues to be essential reading for all students of government, policy analysis, and politics and international relations."--Publisher's description.
Public administration and governing -- Political culture and public administration -- Recruiting public personnel -- Problems of administrative structure -- The politics of bureaucracy -- The bureaucracy and political institutions -- The politics of the budgetary process -- The politics of administrative accountability -- Administrative reform -- The politics of public management.
Includes Bibliographical References and Index.
Keywords: Public administration; Bureaucracy; Comparative government